1.Wykonaj mnożenie i zredukuj wyrazy podobne.
Przykład:(x-5)(x+5)+2xy=x²+5x-5x-25+2xy=x²-25+2xy

a) (3-a)(6-3a)+3a=18-.... -.... + ....+....=
b) (-2+x)(2+x)=...........................................
c) (-4-x)(4+2x)=.......................................
d) (-2-2x)(-4+3x)=....................................
e) (-6-3x)(-5-8x)=...........................................
2.Rozwiąż równania
a) 3x(x-1)=3x²+6
b) -4x(2-x)=2(x²+16)+2x²
c) x²-3(x+1)=-x(2-x)
d) x²-2x=x(x-1)

2

Odpowiedzi

2009-12-17T16:08:24+01:00
A) (3-a)(6-3a)+3a=18-9a-6a+3a²=3a²-15a+18
b) (-2+x)(2+x)=-4-2x+2x+x²=x²-4
c) (-4-x)(4+2x)=-16-8x-4x-2x²=-2x²-12x-16
d) (-2-2x)(-4+3x)=8-6x+8x-6x²=-6x²+2x+8
e) (-6-3x)(-5-8x)=30+48x+15x+24x²=24x²+63x+30
2.Rozwiąż równania
a) 3x(x-1)=3x²+6
....3x²-3x=3x²+6
.....3x²-3x²-3x=6
.........-3x=6/:(-3)
............x=-2
b) -4x(2-x)=2(x²+16)+2x²
.....-8x+4x²=2x²+32+2x²
.......-8x+4x²-2x²-2x²=32
.........-8x=32/:(-8)
...........x=-4
c) x²-3(x+1)=-x(2-x)
.....x²-3x-3=-2x+x²
......x²-x²-3x+2x=3
..........-x=3/:(-1)
...........x=-3
d) x²-2x=x(x-1)
....x²-2x=x²-x
..x²-x²-2x+x=0
...-x=0/;(-1)
....x=0

1 4 1
2009-12-17T16:09:52+01:00
1.
a) (3-a)(6-3a)+3a=18-9a - 6a+3a²+3a=18-9a +3a²
b) (-2+x)(2+x)= -4-2x+2x+x²= -4 + x²
c) (-4-x)(4+2x)= -16 - 8x -4x -2x² = -16-12x - 2x²
d) (-2-2x)(-4+3x)= 8-6x +8x -6x² = 8+2x - 6x²
e) (-6-3x)(-5-8x)= 30 + 48x + 15x + 24x² = 30 +63x + 24x²

2.
a) 3x(x-1)=3x²+6
3x² - 3x=3x²+6
- 3x= 6
x= -2
b) -4x(2-x)=2(x²+16)+2x²
-8x +4x²=2x² + 32 +2x²
-8x= 32
x= -4
c) x²-3(x+1)=-x(2-x)
x² -3x-3=-2x+x²
-x= 3
x= -3
d) x²-2x=x(x-1)
x²-2x=x² -x
-x=0
x=0
2 4 2